2021
DOI: 10.3390/nu13113963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periodic Religious Fasting for Decades on Nutrient Intakes and the Blood Biochemical Profile

Abstract: The aim of the present study was to examine differences and correlations in nutrient intakes and serum parameters related to nutrient intake (lipid profile, vitamins, and trace elements) in 200 lifelong Christian Orthodox Church (COC) fasters with periodic abstinence from certain foods (predominantly of animal origin) for approximately half of the year and 200 non-fasting controls, all of whom did not take dietary supplements. Nutrient intakes were assessed through three-day dietary recalls. Blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Kokkinopoulou et al also showed that fasters exhibited significantly higher triglycerides [ 18 ]. Fasters also had a significantly lower intake of calories [ 18 , 42 ]. Additionally, in a 40-day (fasting and non-fasting days) survey of 36 nuns and monks, a reduction in total cholesterol, a rise in triglycerides and a moderate drop in LDL/HDL during fasting were noted [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kokkinopoulou et al also showed that fasters exhibited significantly higher triglycerides [ 18 ]. Fasters also had a significantly lower intake of calories [ 18 , 42 ]. Additionally, in a 40-day (fasting and non-fasting days) survey of 36 nuns and monks, a reduction in total cholesterol, a rise in triglycerides and a moderate drop in LDL/HDL during fasting were noted [ 41 ].…”
Section: Discussionmentioning
confidence: 99%